(untitled) (مجلة إحالات, 2026)
Epidemics are among the Most important risks That threaten human existence, and hasten its annihilation, where death exercises its presence and power standing on the doorsteps, and humanity has been ravaged by many diseases That have threatened human existence since time immemorial, and raised its existential anxiety and the return of the epidemic with the advent of the time of the Corona pandemic. Literature derives its existence and its transformation from this reality. The creator captured and monitored the epidemic with his pain and his diaries, to turn them into narrative fantasies that simulate the diaries of the struggle with the darkness of the epidemic and death.